Fourteen-year follow-up of a child with acroscyphodysplasia with emphasis on the need for multidisciplinary management: a case report - Katina Kartalias; Austin P. Gillies; Maria T. Peña; Andrea Estrada; Dorothy I. Bulas; Carlos R. Ferreira; Laura L. Tosi (BMC, 2020)
Abstract Background Acroscyphodysplasia has been described as a phenotypic variant of acrodysostosis type 2 and pseudohypoparathyroidism. In acrodysostosis, skeletal features can include brachydactyly, facial hypoplasia, cone-shaped epiphyses, short stature, and advanced bone age. To date, reports on this disorder have focused on phenotypic findings, endocrine changes, and genetic variation. We present a 14-year overview of a patient, from birth to skeletal maturity, with acroscyphodysplasia, noting the significant orthopaedic challenges and the need for a multidisciplinary team, including specialists in genetics, orthopaedics, endocrinology, and otolaryngology, to optimize long-term outcomes. Case presentation The patient presented as a newborn with dysmorphic facial features, including severe midface hypoplasia, malar flattening, nasal stenosis, and feeding difficulties. Radiologic findings were initially subtle, and a skeletal survey performed at age 7 months was initially considered normal. Genetic evaluation revealed a variant in PDE4D and subsequent pseudohypoparathyroidism. The patient presented to the department of orthopaedics, at age 2 years 9 months with a leg length discrepancy, right knee contracture, and severely crouched gait. Radiographs demonstrated cone-shaped epiphyses of the right distal femur and proximal tibia, but no evidence of growth plate changes in the left leg. The child developed early posterior epiphyseal arrest on the right side and required multiple surgical interventions to achieve neutral extension. Her left distal femur developed late posterior physeal arrest and secondary contracture without evidence of schypho deformity, which improved with anterior screw epiphysiodesis. The child required numerous orthopaedic surgical interventions to achieve full knee extension bilaterally. At age 13 years 11 months, she was an independent ambulator with erect posture. The child underwent numerous otolaryngology procedures and will require significant ongoing care. She has moderate intellectual disability. Discussion and conclusions Key challenges in the management of this case included the subtle changes on initial skeletal survey and the marked asymmetry of her deformity. While cone-shaped epiphyses are a hallmark of acrodysostosis, posterior tethering/growth arrest of the posterior distal femur has not been previously reported. Correction of the secondary knee contracture was essential to improve ambulation. Children with acroscyphodysplasia require a multidisciplinary approach, including radiology, genetics, orthopaedics, otolaryngology, and endocrinology specialties.